The Role of Instructional Leadership in Enhancing Teacher Learning Services for Improved Educational Outcomes: A Literature Reviews - Agusli, Agusli; Hadiyanto, Hadiyanto; Sulastri, Sulastri (International Journal of Educational Dynamics, 2024)
This study examines the role of instructional leadership in improving teacher learning services to enhance the quality of education. The objective is to explore how principals, as instructional leaders, foster teacher professionalism, improve instructional materials, and create conducive learning environments. A literature reviews method was used to gather and analyze data from relevant academic sources, including books, articles, and policy documents. Key findings highlight that instructional leadership directly contributes to teacher professional development by encouraging innovative teaching practices, facilitating collaboration, and providing feedback for continuous improvement. This leadership approach enhances teacher's capacity to address student needs effectively, apply innovative teaching methods, and foster both academic and personal growth in students. Furthermore, the study identifies five components of effective instructional leadership: focusing on learning, fostering collaboration, analyzing student achievement, supporting teacher development, and adapting curricula and assessments to current demands. These actions ultimately improve the quality of teacher learning services and positively impact student achievement. The study concludes that instructional leadership is a critical factor in achieving high-quality education, underscoring the interconnected roles of principals and teachers in the learning process.